Pengetahuan tentang Komplikasi Diabetes Mellitus dengan Tingkat depresi pada Pasien Diabetes Mellitus - Ni Made Wedri (Jurnal Gema Keperawatan, 2015)
Purpose of research is to know about relation between knowledge levels about DM complications with depression level of DM sufferer in “Poliklinik Interna Sanglah” Hospital Denpasar. Type non-experimental studies correlation with consecutive sampling, large sample 65 and the analysis Kendal tau. Result of got, value of coefficient correlation is – 0,420. Negative value means the increase of one variable followed by decrease of the other variable significance (2-tailed) = 0,01 where this value are less small than 0,05. It’s means Ho pushed away and Ha accepted, so the conclusion there was a relationship between knowledge level about complication of DM and depression level of DM sufferer. Depression level of DM sufferer will be increasing if they have less knowledge and information about the disease.